Cost Estimates of Establishing and Producing Thai Guavas in Florida, 2014 - Stella Garcia; Edward Evans; Jonathan Crane (EDIS)
The white Thai guava variety, which is very popular in the Asian market, is beginning to expand into mainstream markets. It has quick, high yields, is easily propagated, and is tolerant to moisture, stress, and soil salinity. But even though it offers favorable returns, there has been little information about the cost of production. This 7-page fact sheet identifies inputs, costs, and yields considered to be typical of a well-managed five-acre Thai guava orchard in south Florida. Written by Stella Garcia, Edward A. Evans, and Jonathan Crane, and published by the UF Department of Food and Resource Economics, August 2016.